2014
DOI: 10.15403/jgld.2014.1121.232.1hjmp
|View full text |Cite
|
Sign up to set email alerts
|

Open-Access Flexible Sigmoidoscopy Frequently Leads to Additional Colonoscopy in Symptomatic Patients over 50 years

Abstract: Background & Aims: General practitioners (GPs) in the Netherlands have open access to flexiblesigmoidoscopy (FS) for patients with lower gastrointestinal symptoms, but not to colonoscopy. This studywas performed to investigate the yield of FS in GP-referred patients, to evaluate the proportion of patientsin whom additional colonoscopy was performed and to investigate whether there was a subgroup of patients referred for symptoms with a low risk of detecting significant findings.Methods: All patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…In the present study, it was observed that there were no specific clinical symptoms in older patients with colorectal polyps, and the majority of patients presented with changes in bowel habit or other symptoms, including abdominal pain, constipation, rectal bleeding or hematochezia, and positive fecal occult blood, which was similar to findings reported in other retrospective studies (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, it was observed that there were no specific clinical symptoms in older patients with colorectal polyps, and the majority of patients presented with changes in bowel habit or other symptoms, including abdominal pain, constipation, rectal bleeding or hematochezia, and positive fecal occult blood, which was similar to findings reported in other retrospective studies (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…9,11 However, fear of missing proximal cancers remains, with 20–70% of patients proceeding to WCI following flexible sigmoidoscopy. 8,9,11,21 This negates the convenience and cost-effectiveness of flexible sigmoidoscopy, particularly as subsequent WCI has a very low cancer yield. 8,9 To address the fear of missing cancers in patients examined solely by flexible sigmoidoscopy, we sought to determine in which patients the yield of proximal cancer and the probability of missing proximal cancer is low.…”
Section: Discussionmentioning
confidence: 99%
“…Examinations failing to reach the sigmoid–descending colon junction are, however, typically deemed incomplete, 20,23,25 prompting subsequent whole-colon completion examination. 8,9,21 It is worth noting that, although studies have reported high rates of incomplete examinations due to pain, faeces, or scope looping, these were based on flexible sigmoidoscopy performed over 10 years ago. 23,25 There are now remedies to avoid these scenarios.…”
Section: Discussionmentioning
confidence: 99%